Webometric Analysis of Institutional Repositories of Malaysian Public Universities - Ismail, Nor Azman; Ramzi, Nurina Izzati; Mohamed, Su Elya Namira; Razak, Mohd Sharul Hafiz (DESIDOC Journal of Library & Information Technology, 2021)
An institutional repository (IR) is one of the resources available in most university libraries that have attracted external publishers, search engines and social media to link, share and index IR content. The traditional citation-based indicators of a publication may not reflect the IR quality and have led to the creation of new indicators such as webometrics or web metrics. This study aims to analyse and explore Malaysia’s public university IR visibility, the numbers of an external link, page count, PDF count and URL web mention. We utilised backlinks web crawler and web search engine to collect raw data. A visualisation was created using the force-directed graphing method to interpret the IR network in the webspace. This study revealed that two research universities, Universiti Malaya (UM) and Universiti Putra Malaysia (UPM), dominate web visibility based on webometrics indicators. All non-research universities are at the bottom of the rankings. This study shows institutional repositories from research universities are more visible in academic social networks and digital library sites. In contrast, non-research universities need to improve their visibility by mapping the universities’ IRs websites through hyperlink exchange and collaboration activities between each university and promoting the university publication to the academic social network sites.